Electromechanical and Dynamic Characterization of In-House-Fabricated Amplified Piezo Actuator. (3rd January 2012) - Panda, P. K.; Sahoo, B.; Raja, S.; M. P., Vijaya Kumar; Shankar, V.
Abstract : A diamond-shaped amplified piezo actuator (APA) fabricated using six multilayered piezo stacks with maximum displacement of 173 μ m at 175 V and the amplification factor of 4.3. The dynamic characterization of the actuator was carried out at different frequencies (100 Hz–1 kHz) and at different AC voltages (20 V–40 V). The actuator response over this frequency range was found neat, without attenuation of the signal. Numerical modeling of multilayered stack actuator was carried out using empirical equations, and the electromechanical analysis was carried out using ABAQUS software. The block force of the APA was 81 N, calculated by electromechanical analysis. This is similar to that calculated by dynamic characterization method.